ASSERTIVE ILLOCUTIONARY ACTS ON INTERRUPTION BY JOE BIDEN IN THE 2020 FIRST PRESIDENTIAL DEBATE - Fania Yulistiana; Widyastuti (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2022)
In a debate, interruption is a vital element because its utterance carries a distinct meaning. This study aims to demonstrate the presence of assertive illocutionary acts in Joe Biden's interruptions in the 2020 First Presidential Debate by identifying the type of interruption and assertive function contained within each interruption. This study utilizes the theory of assertive illocutionary acts by Searle and interruptions by Ferguson. The data were derived from Joe Biden's remarks in the 2020 First Presidential Debate. The results indicate that Joe Biden's interruption contains all functions of assertive illocutionary acts that aid in communicating the meaning of his utterances. The outcomes reveal that Joe Biden performed 21 interruptions, with the most parts being overlap interruptions (13 times), followed by simple interruptions (6 times), and the fewest being butting-in interruptions (2 times). In the interruption conducted by Joe Biden, assertive illocutionary speech acts were found with stating being the most dominant type (11 times), followed by claiming (5 times), complaining (2 times), reporting (1 time), explaining (1 time), and suggesting (1 time).